Cytological evaluation of p16Ink4a in precancerous lesions of the cervix: Conventional papanicolaou smears - Seema Singhal; Vinod Kumar Arora (Apollo Medicine)
Background: Cancer of the uterine cervix is the second most common cancer among women worldwide. More than three fourths of these patients are diagnosed at advanced stages, leading to poor prospects of long term survival and cure. Introduction of Papanicolaou (Pap test) cytological screening for cervical precancerous lesions has significantly reduced the incidence and mortality of cervical cancer. Human papillomavirus (HPV) DNA testing has been recently demonstrated to be efficient to be integrated into screening programs, so it can be used to triage women with equivocal cytological abnormalities and also identifies women at risk of residual or recurrent disease after treatment of cervical intraepithelial neoplasia. However, it fails into triage low grade lesions. HPV DNA test confirms infection by the virus, present in 99% of cases. However, it does not discriminate between transient and persistent infection as it is crucial because it is the persistent infection which progresses to neoplasia. Histological assessment of cervical biopsy that is considered as “gold standard” can be hampered by intra and inter observer variability. A more specific triage marker is required to identify women who would need colposcopy. Hence, p16INK4a has emerged as a new diagnostic and prognostic biomarker. Aims and objectives: This study was conducted to evaluate the utility of staining of p16INK4a on conventional Pap smears and its comparison with corresponding biopsies. Material and Methods: 50 cases of conventional Papanicolaou stained cervical smears cases were randomly selected from the archive of cytopathology laboratory. The cervical smears were re-evaluated for adequacy, preservation of cells, cytomorphology and various lesions were categorized according to The Bethesda system 2001 (TBS) classification. Consecutive such cases were selected for which both cytological and histological material were available. Immunostaining of cervical cytological specimens for p16 was performed using monoclonal murine antibody, clone 16P04, JC2. Ready to use antibody was used for immunostaining as per manufacturer's protocol. Results: Out of the 50 smears of preneoplastic and invasive lesions, ASCUS was seen in 5 cases, LSIL in 10 cases, HSIL in 20 cases, SCC in 20 cases and AGUS in 5 cases. Of the 5 cases of ASCUS, histopathology showed 3 chronic cervicitis and 1 each in CIN-1 and CIN-2. Histopathological diagnosis of 10 cases of LSIL showed 6 CIN-1 and 2 each in CIN-2 and chronic cervicitis. Similarly, for 10 cases of HSIL, 3 were CIN-2, 5 CIN-3 and 2 SCC. All 20 cases of carcinoma showed SCC while 5 cases of AGUS showed 4 chronic cervicitis and one adenocarcinoma. Immunohistochemical staining of p16INK4A showed weak positivity in 3 cases of chronic cervicitis and 4 cases of CIN-1. In CIN-2 cases, 66.67% showed strong positivity, CIN-3 showed 80% while both carcinoma and adenocarcinoma showed 100% strong positivity. The sensitivity of immunohistochemical staining of p16INK4A was 77.5%, specificity was 100%, PPV 100% and NPV 52.6%. The relation between histological and cytological immunostaining of p16INK4A. Conclusion: p16INK4A is a reliable marker for dysplastic squamous and glandular cervical cells both in tissue sections and in cervical smears. p16 immunostaining can be easily performed on CPS, and there is high concordance of positivity on smears and tissue sections.